Hydrogen reduction behavior of W/Y2O3 powder synthesized by ultrasonic spray pyrolysis. (February 2021) - Choi, Won June; Kim, Jeong Hyun; Lee, Hojun; Park, Chun Woong; Lee, Young-In; Byun, Jongmin
Abstract: In this study, hydrogen reduction behavior of W/Y2 O3 powder was investigated. Phase transformation of WO3 /Y2 O3 powder was observed during the hydrogen reduction process in the temperature range of 400–800 °C for up to 5 h. The reduction behavior was investigated by the morphology images and the x-ray diffraction (XRD) patterns of the reduced powders at each step. The reduction of WO3 /Y2 O3 powder was started from the outer region of powder, and the crack was occurred at outer region due to the transformation, which was able to be explained by crackling core model. The particle size of W/Y2 O3 decreased due to the addition of Y2 O3 particle compared to that of W powder. The activation energy of WO3 /Y2 O3 powder was calculated via temperature programmed reduction (TPR) analysis, and WO3 /Y2 O3 and WO3 powder had a difference in activation energy calculated from first peaks in TPR analysis. The addition of Y2 O3 particle affected the reduction behavior, especially reduction of WO3 phase to WOx (2 ≤ x < 3) phases. Highlights: Hydrogen reduction behavior of WO3 /Y2 O3 powder, which was synthesized by ultrasonic spray pyrolysis was investigated. The reduction behavior of WO3 /Y2 O3 powder was followed by the crackling core model, which was observed by SEM analysis. The activation energy of WO3 /Y2 O3 powder during hydrogen reduction was calculated using TPR analysis. The addition of Y2 O3 particle changed the reduction mechanism of WO3 phase.